2020
DOI: 10.1101/2020.08.20.258798
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Object manifold geometry across the mouse cortical visual hierarchy

Abstract: Despite variations in appearance we robustly recognize objects. Neuronal populations responding to objects presented under varying conditions form object manifolds and hierarchically organized visual areas are thought to untangle pixel intensities into linearly decodable object representations. However, the associated changes in the geometry of object manifolds along the cortex remain unknown. Using home cage training we showed that mice are capable of invariant object recognition. We simultaneously recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…S11a to S11b (6,73,76). We note that (77) recently studied the related but distinct quantity of “object manifold dimensionality” computed across transformations of a visual object, in optical recordings from some of these same areas, and found distinct trends for that quantity that are also consistent with dimensionality playing a role in visual information processing. These results underscore the functional value of both dimensionality mechanisms and the visual hierarchy per se (54).…”
Section: Introductionsupporting
confidence: 56%
“…S11a to S11b (6,73,76). We note that (77) recently studied the related but distinct quantity of “object manifold dimensionality” computed across transformations of a visual object, in optical recordings from some of these same areas, and found distinct trends for that quantity that are also consistent with dimensionality playing a role in visual information processing. These results underscore the functional value of both dimensionality mechanisms and the visual hierarchy per se (54).…”
Section: Introductionsupporting
confidence: 56%
“…A further improvement may be opsin-matched filters. 66 Mouse camera movies as natural stimuli Stimuli used in vision research cover a broad spectrum, ranging from artificial stimuli, like gratings and noise (reviewed in Rust and Movshon 67 ) or screen-rendered 3D objects, 68,69 to more naturalistic ones. [70][71][72] The movies recorded here represent suitable natural stimuli to probe mouse vision: (1) they were recorded outdoors in places where mice can be seen at daytime and (2) contain the spectral bands perceived by mice.…”
Section: Recording Natural Scenesmentioning
confidence: 99%
“…Critically, during the last decade, a number of functional and anatomical studies in mice and rats have convincingly shown that visual information is processed in a hierarchical fashion across the many extrastriate visual areas that, in rodents, surround V1 53,54 . In particular, it has been shown that, along the progression of visual areas that run laterally to rat V1, many key tuning and coding properties evolve according to what is expected for a ventral-like, object-processing pathway 32,33,[55][56][57] , including the ability to support invariant visual object recognition-a finding that has been recently replicated in mice 58 .…”
Section: Strong Adaptationmentioning
confidence: 99%